PERAN P4MI SIDOARJO MENANGANI KASUS PELANGGARAN HAK KONTRAK KERJA PEKERJA MIGRAN INDONESIA HONG KONG 2025: THE ROLE OF P4MI SIDOARJO IN HANDLING CASES OF VIOLATION OF LABOR CONTRACT RIGHTS OF INDONESIAN MIGRANT WORKERS IN HONG KONG 2025 - Dhiaulhaqi An Nazhmi; Slamet Mulyono Redjosari (Journal of Law and Border Protection, 2025)
This study discusses the role of P4MI Sidoarjo in handling cases of violations of labor contract rights experienced by Indonesian migrant workers in Hong Kong in 2025. This study departs from the many cases of complaints from migrant workers, especially in Hong Kong, who often experience unilateral termination of employment, salary deductions, and not getting basic rights according to the contract. Using a descriptive qualitative approach, data was collected through interviews with P4MI Sidoarjo staff, direct observation, as well as searching for related documents and news. The results show that P4MI Sidoarjo plays an active role as a place of complaint, mediator, and companion for migrant workers who experience problems. One of the cases raised is the case of Putri, a migrant worker who was unilaterally repatriated and did not get her rights. P4MI Sidoarjo followed up on the complaint by facilitating clarification between the worker, agency and related parties. However, this study also found that the protection of migrant workers still faces challenges, especially in terms of enforcing rights and providing fair compensation. Therefore, the role of P4MI is crucial to ensure legal, social and economic protection for Indonesian migrant workers abroad